Perancangan Display LED Dot Matrix menggunakan Mikrokontroler ATmega32 - ., Benny Julisha Pratida (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2013)
Abstract – Nowadays, the forwarding of information media is an important thing in fulfilling the requirement of information everyday. Media of  information also has various forms from conventional like poster, pamphlet, or baliho, even electronical media like Neon lamp, Display Seven Segment and Display LED Dot Matrix. Display LED Dot Matrix has many benefits in the case of its use, for example its information can be updated easily through computer and doesn't need big electricity. The intention of this research is how to design hardware and software for Display LED Dot Matrix in order to present letter character and numeral as according to the requirement of user from a computer. The mikrokontroler which used is mikrokontroler ATmega32 as master controller from system and the application of Visual Basic as the application of character data sender which will be presented to Display LED Dot Matrix. For updating the information which will be presented, the user just typing character data which will be sent to the application which is applied by Visual Basic. This application was called Input Data Matrix or IDM. Based on this research which has been done, the character which will be presented by this application has maximum  amount of 200 characters  including the space. While the data transfer time needed to sends character data or article on Display LED Dot Matrix is 10,67 seconds. Keywords - Display LED Dot Matrix, Mikrokontroler ATmega32, MAX7219